Technique of applying protective coatings on diesel piston rings - Еlena M. Zubrilina; Тatyana A. Czecha; Mikhail V. Dobychin; Igor N. Kravchenko (Advanced Engineering Research)
The work objective is to search for new non-conventional structural low-activated materials. The dispersion-strengthened microalloyed chrome-based alloys that show high mechanical-and-physical properties under the initial condition are described. The results of the comparative studies of the chromium structural behavior obtained by the galvanic and hot spraying methods applied to the piston rings are quoted. This allows identify and assess the advantages of these coatings depending on the performance. Chromium rings wear - engine operating time experimental dependences are shown. The results of the quick and full-scale testing of various engines to determine the effect of the chromium coating composition on the size and behavior of the friction factor depending on the load are described. The feasibility of applying the diesel piston ring coatings under study is assessed.